2006
DOI: 10.1111/j.1600-0501.2006.01318.x
|View full text |Cite
|
Sign up to set email alerts
|

Therapy of peri‐implantitis with resective surgery. A 3‐year clinical trial on rough screw‐shaped oral implants. Part II: radiographic outcome

Abstract: The results of this radiographic research suggested that implantoplasty was an effective treatment of peri-implant infections and peri-implantitis progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
433
6
27

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(477 citation statements)
references
References 30 publications
11
433
6
27
Order By: Relevance
“…2,68,72 Currently, different surgical treatment modalities have been proposed and have shown promising results. 16,[73][74][75][76][77] However, long-term controlled studies are needed to validate which treatment modality may be optimal, given the different clinical scenarios. It has been suggested, as with many inflammatory diseases, that the earlier the diagnosis and intervention, the better the treatment outcome.…”
Section: Discussionmentioning
confidence: 99%
“…2,68,72 Currently, different surgical treatment modalities have been proposed and have shown promising results. 16,[73][74][75][76][77] However, long-term controlled studies are needed to validate which treatment modality may be optimal, given the different clinical scenarios. It has been suggested, as with many inflammatory diseases, that the earlier the diagnosis and intervention, the better the treatment outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Peri-implant dokuların iyileşmesini hızlandırmak için biyofilmin uzaklaştırıl-ması yani implant yüzeyinin dekontamine edilmesi gerekmektedir. Mekanik yolla dekontaminasyon, özel uçlara sahip küretler ve ultrasonik cihazlar yardımıyla ya da implant yüzeyinin frezlerle düzleştirilme-si (implantoplasti) ile gerçekleştirilmektedir (46). Dekontaminasyon aynı zamanda sitrik asit, hidrojen peroksit ve klorheksidin ile kimyasal yolla ya da lazer aracılığıyla uygulanabilmektedir (Resim 5) (47).…”
Section: Peri-implantitis Tedavisiunclassified
“…11,19,20 Where mechanical debridement is undertaken, plastic or titanium curettes have been recommended to avoid damaging the implant surface. 10 However, Romeo et al 21 have reported promising results following the deliberate removal of the implant surface. Guided bone regeneration may be used in conjunction with surgical debridement and this may result in greater bony infill although re-osseointegration is unlikely to occur.…”
Section: Peri-implantitismentioning
confidence: 99%
“…20 Studies suggest that surgical debridement may be successful in 60-100% of cases. 20,21 Fistulae Fistulae have been reported at the level of the implant-abutment interface in 1% of cases (study duration not reported) 5 (Fig. 4) and they are usually associated with loose abutments screws or ill-fitting frameworks.…”
Section: Peri-implantitismentioning
confidence: 99%